Thermoluminescence response of ytterbium-doped silicon dioxide fiber - Saeed, Mohammad Alam (Maik Nauka Publishing / Springer SBM, 2015)
In this study, thermoluminescence properties of Yb-doped of SiO2 optical fiber such as linearity, sensitivity and dose response have been investigated. Samples were placed in the gelatin capsules to irradiate with photons from Cobalt-60 of the dose range between 10-100 Gy. The beams were provided by Gammacell 220, available at Universiti Kebangsaan Malaysia, Bangi, Malaysia. The glow curves were analyzed to determine various characteristics of the thermoluminescence. The TL response as a function of dose is linear up to 40 Gy. The sensitivity of Yb-doped optical fiber is 0.136 nC mg-1 Gy-1